Illegal Immigrants Between Indonesia Australia: How the Law and Policy Solving the Problems? - Wicaksono, Dava Irfani (Fakultas Hukum Universitas Negeri Semarang, 2021)
In the recent years, cases of illegal immigrants from Indonesia to Australia have been escalated, so Australia itself created a rule that functioned for those dark or illegal immigrants were unable to enter the Territory Australia. The rules are the policy of the rule of the country and the third policy and whether Indonesia itself is a sovereign state that has had an excellent policy in resolving cases of illegal or ilelal immigrants within its territory Own. With the methodology of the juridical approach of Normative, using primary and secondary data, studying and evaluating several principles and legal norms relating to the sovereignty of the State and illegal immigrants obtained from libraries and regulations Then in a qualitative descriptive analysis to derive conclusions. In Indonesia's policy must have been regulated through LAW No. 6 of 2011 on immigration, which is where there is a solution in the case of dark immigrants. But this is still not effective in handling the issue of illegal immigrants and is a partial where it still makes illegal immigrants or illegally victims of casualties and the absence of sanctions and deterrent effects against them. Indonesia should make the national sovereignty principle a guideline for making regulatory policies regarding illegal immigrants.